Remote estimation of reconnection parameters in the Earth's magnetotail: model and observations - A. Alexandrova; A. Alexandrova; R. Nakamura; V. S. Semenov; I. V. Kubyshkin; S. Apatenkov; E. V. Panov; D. Korovinskiy; H. Biernat; W. Baumjohann; K.-H. Glassmeier; K.-H. Glassmeier; et al. (Annales Geophysicae, 2012)
We develop a method to estimate the reconnected magnetic flux and the location of the reconnection site using properties of magnetic field and plasma velocity disturbances in the regions surrounding the reconnection plasma flow. Our analysis is based on a 3-D non-steady reconnection model with a finite-sized X-line length. In this framework, we obtain a system of equations capturing the relationships between the disturbances of the magnetic field and plasma flow from one side and the reconnection characteristics from another side. These equations allow us to determine the reconnection characteristics from one-point remote observations of the reconnection fast flow, propagated in the magnetotail current sheet. We apply the model to magnetic field and plasma observations at (−43, −11.2, −6.9) RE GSM obtained by the THEMIS/ARTEMIS spacecraft, located in the tail lobe during a substorm event. We found that the reconnection region was located at ~ (−27, 3.5, 0) RE GSM. The X-line appeared to be close to the local time of the substorm current wedge identified from ground-based observations. We estimated the total magnetic flux, which was reconnected in the event as ~5 MWb. That corresponds to a small fraction of the total amount of magnetic flux transferred during a substorm.